2015
DOI: 10.5194/hess-19-4493-2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mountain tea plantations on nutrient cycling at upstream watersheds

Abstract: Abstract. The expansion of agriculture to rugged mountains can exacerbate negative impacts of agricultural activities on ecosystem function. In this study, we monitored streamwater and rainfall chemistry of mountain watersheds at the Feitsui Reservoir Watershed in northern Taiwan to examine the effects of agriculture on watershed nutrient cycling. We found that the greater the proportion of tea plantation cover, the higher the concentrations of fertilizer-associated ions (NO − 3 , K + ) in streamwater of the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…et al, Lu et al, 2017). However, our results showed that in many cases such models would not perform well during extreme conditions such as during typhoons.…”
Section: Unpredictability Of Hydrochemical Response To Climate Extremescontrasting
confidence: 54%
“…et al, Lu et al, 2017). However, our results showed that in many cases such models would not perform well during extreme conditions such as during typhoons.…”
Section: Unpredictability Of Hydrochemical Response To Climate Extremescontrasting
confidence: 54%
“…Many hydrological models are constructed primarily based on non-extreme conditions or on a combination of both extreme and non-extreme conditions (Wade et al, 2006; Lu et al, 2017). However, our results showed that in many cases such models would not perform well during extreme conditions such as during typhoons.…”
Section: Unpredictability Of Hydrochemical Response To Climate Extremesmentioning
confidence: 74%
“…Higher SRP flux occurred in typhoon storm events with longer antecedent dry days and lower API 5 values. This may explain the re-mobilization of P-rich bed-sediments that accumulated within the river channel from the upstream to the downstream of main inflow river during the summer low-flow periods [46][47][48][49]. Previous work also suggest that channel fine-grained sediment potentially stores phosphorus, ready to be remobilized during storm events [50][51][52].…”
Section: Discussionmentioning
confidence: 89%